Объяснение:
1. a₁=-2 a₁₀=16 a₁₂=?
a₁₀=a₁+(10-1)*d=16
-2+9*d=16
9*d=18 |÷9
d=2 ⇒
a₁₂=a₁+(12-1)*d=-2+11*2=-2+22=20
ответ: а₁₂=20.
2. a₇=43 a₁₅=3 a₁₂=?
{a₇=a₁+6d=43
{a₁₅=a₁+14d=3
Вычитаем из нижнего уравнения верхнее:
8d=-40 |÷8
d=-5 ⇒
a₁+6*(-5)=43
a₁-30=43
a₁=73
a₁₂=73+11*(-5)=73-55=18
ответ: a₁₂=18.
3. a₁=30 d=-0,4 a₁₂=?
a₁₂=30+11*(-0,4)=30-4,4=25,6
ответ: a₁₂=25,6.
4. a₁₀=9,5 S₁₀=50 a₁₂=?
Sn=(a₁+an)*n/2
(a₁+9,5)*10/2=50
(a₁+9,5)*5=50 |÷5
a₁+9,5=10
a₁=0,5
a₁₀=a₁+9d=9,5
0,5+9d=9,5
9d=9 |÷9
d=1 ⇒
a₁₂=a₁+11d=0,5+11*1=0,5+11=11,5.
ответ: а₁₂=11,5.
b3=b1*q^2
b2=b1*q
b4=b1*q^3
b1*q^2–b1=24; b1(q^2–1)=24
b1*q–b1*q^3=8; b1*q(1–q^2)=8
Разделим первое уравнение на второе:
(q^2–1)/q(1–q^2)=3
q^2–1=3q(1–q^2)
q^2–1=–3q(q^2–1)
–3q=1
q=-1/3
b1=24/(q^2–1)=24/(1/9–1)=24:(-8/9)=
=-27
b2=-27*(-1/3)=9
b3=9*(-1/3)=-3
b4=-3*(-1/3)=1
ответ: -27; 9; -3; 1